Model Testing and Numerical Simulation of the Bearing Characteristics of Screw-Core Cement Mixing Pile - Luoan Wu; Yue Gao; Yaohui Du; Junjie Xuan; Jiu Nao; Shibo Li; Jinhao Li; Yanqi Wang; Hao Zhang; Lei Cao; Cheng Meng; Zewei Yang (Buildings)
The screw-core mixing pile, which enhances traditional smooth-surface rigid piles by introducing a threaded surface, has been rapidly applied in China. Indoor model testing and numerical simulation techniques are used to perform static load tests on single piles to analyze the load–settlement relationship between the new screw-core mixing pile and the traditional circular-core mixing pile. The study examines the axial force distribution between the pile core and the mixing pile shell and establishes a bearing capacity model for screw-core mixing piles. Additionally, model piles with six different thread height ratios (w/d, where w is the thread width and d is the internal diameter of the screw-core) are developed using finite element simulation software to analyze the effect of thread height ratio on the bearing capacity of screw-core mixing piles. The influence of the height ratio on the bearing capacity of screw-core mixing piles is discussed in detail. The results indicate the following: (1) Due to differences in the pile core structure, the bearing capacity of the screw-core mixing pile is 1.44 times greater than that of the circular-core mixing pile. (2) When the vertical load is small, both the pile core and the mixing pile shell share the load; however, as the vertical load increases, the axial force gradually concentrates in the pile core, with the screw core showing a higher load-bearing capacity than the circular-core. (3) Under vertical load, the settlement of the screw-core mixing pile decreases stepwise from the top of the pile down to the surrounding area, demonstrating that the screw-core is more effective than the circular core. (4) The increase in thread height ratio significantly enhances the bearing capacity of the screw-core mixing pile. However, considering material limitations and engineering costs, the optimal thread height ratio should be determined based on actual bearing capacity requirements and soil conditions.